Automated sputum screening using the BD FocalPointTM Slide Profiler : correlation with transbronchial and transthoracic needle aspirates in a high risk population - Neethling, Greta Sophie (Stellenbosch : Stellenbosch University, 2014)
Thesis (MMed)--Stellenbosch University, 2014.